2000
DOI: 10.1034/j.1600-0560.2000.027001054.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple eruptive dermatofibromas in a patient with HIV infection: case report and literature review

Abstract: Multiple eruptive dermatofibromas have been reported in the setting of autoimmune diseases treated with immunosuppressive drugs and more recently in the course of human immunodeficiency virus (HIV) infection. We report herein the ninth case of multiple eruptive dermato fibromas associated with HIV infection. The relevant literature is reviewed and the differences of these lesions from "ordinary" dermatofibromas are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 9 publications
0
31
0
4
Order By: Relevance
“…It occurs most often as a solitary lesion in otherwise healthy persons. MEDFs are rare and have been reported in association with autoimmune and neoplastic diseases, with and without immunosuppressive treatment, HIV infections and other conditions, including hydronephrosis, diabetes, hypercholesterolemia, obesity, atopic dermatitis and pregnancy [1, 2, 3, 4, 5]. These conditions affect the immune status, suggesting that altered immunity may play a role in the pathogenesis of MEDF [1, 3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs most often as a solitary lesion in otherwise healthy persons. MEDFs are rare and have been reported in association with autoimmune and neoplastic diseases, with and without immunosuppressive treatment, HIV infections and other conditions, including hydronephrosis, diabetes, hypercholesterolemia, obesity, atopic dermatitis and pregnancy [1, 2, 3, 4, 5]. These conditions affect the immune status, suggesting that altered immunity may play a role in the pathogenesis of MEDF [1, 3].…”
Section: Discussionmentioning
confidence: 99%
“…It most often occurs as a solitary lesion in otherwise healthy persons. Multiple eruptive dermatofibromas (MEDFs) are rare and have been thought to be associated with altered immunity [1, 2, 3, 4, 5]. It has been reported that dermatofibrosarcoma protuberans (DFSP) is positive for CD34 but not for factor X IIIa, whereas DF is positive for factor X IIIa but not for CD34 [6, 7, 8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…MEDF usually occurs in immunocompromised patients with HIV infection or receiving an immunosuppressive drug therapy [11, 12, 13, 14, 15], making its clinical and/or pathological distinction from KS challenging [16]. We present a patient with MEDF who showed no clinical and laboratory signs of immunodeficiency but was seropositive for HHV-8 antibodies and demonstrated HHV-8 DNA both in his blood and lesional skin.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of multiple eruptive DF (MEDF) is rare. Since the initial observation of Cohen 1 of the association among MEDFs, autoimmune diseases, and immunosuppressive therapy, MEDFs have been associated with autoimmune diseases, 1-14 immunosuppressant therapy, 1,2,[4][5][6][7][8][9][10][11]13,14 HIV infection, 8,[15][16][17][18][19][20][21] hematologic malignancy, [22][23][24] pregnancy, 25 and other conditions. MEDFs may be related to the altered immune status of these conditions, although the pathogenesis is uncertain.…”
mentioning
confidence: 99%